2010
DOI: 10.1097/wnf.0b013e3181de8966
|View full text |Cite
|
Sign up to set email alerts
|

Labile Anger During Interferon Alfa Treatment is Associated With a Polymorphism in Tumor Necrosis Factor α

Abstract: Objective-Inflammatory cytokines may influence both labile anger and depression. Both psychiatric conditions can occur during interferon-alpha (IFN-α) based treatments. Evidence also indicates a central nervous system role for TNF-α, whose expression may be increased by IFN-α. A polymorphism in the promoter region of TNF-α has been associated with various inflammatory illnesses. We therefore hypothesized that this TNF-α polymorphism would influence susceptibility to psychiatric symptoms during IFN-α therapy.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 105 publications
2
34
0
Order By: Relevance
“…Consistent with this, we have found that polymorphisms affecting TNF-a and IL-28b are associated with specific mood-related symptom clusters in individuals receiving IFN-a (Lotrich et al, 2010;Lotrich et al, 2011). Also, we have found that a serotonin reuptake promoter polymorphism (5-HTTLPR) is associated with increased Beck Depression Inventory scores during IFN-a therapy ), but another group did not find an association using the Hospital Anxiety Depression Scale (Kraus et al, 2007).…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…Consistent with this, we have found that polymorphisms affecting TNF-a and IL-28b are associated with specific mood-related symptom clusters in individuals receiving IFN-a (Lotrich et al, 2010;Lotrich et al, 2011). Also, we have found that a serotonin reuptake promoter polymorphism (5-HTTLPR) is associated with increased Beck Depression Inventory scores during IFN-a therapy ), but another group did not find an association using the Hospital Anxiety Depression Scale (Kraus et al, 2007).…”
Section: Introductionsupporting
confidence: 64%
“…Several quantitative assessments, rather than a categorical outcome of MDD, were selected because of increasing evidence that many genetic vulnerabilities may be associated with specific symptom clusters during IFN-a therapy (Lotrich et al, 2010;Lotrich et al, 2011;Su et al, 2010). Subjects were given the opportunity to either mail in questionnaire results or complete them on routine clinic days.…”
Section: Depression Assessmentmentioning
confidence: 99%
“…LPS-stimulated TNFα expression was positively correlated with physical aggression, verbal aggression, and hostility. In other studies, LPS-induced increases in TNFα correlated with stress-induced emotion arousal,(Moons et al, 2010; Suarez et al, 2006) and interferon-induced labile anger (Lotrich et al, 2010). …”
Section: Introductionmentioning
confidence: 72%
“…The 2010 work of Lotrich et al has demonstrated that presence of a polymorphism of the TNF-a gene, previously associated with increased TNF-a response to inflammation, is associated with a greater increase in labile anger with interferon treatment. This is speculated by the authors to be mediated by central TNF-a levels as there was no correlation with circulating levels of TNF-a (Lotrich et al, 2010). In addition, baseline ratios of arachidonic acid (an x-6 fatty acid) to eicosapentaenoic acid and docosahexaenoic acid (x-3 fatty acids) are correlated with increased labile anger after interferon treatment and subjects with a higher ratio had significantly more labile anger and irritability after interferon treatment.…”
Section: Irritability and Inflammationmentioning
confidence: 89%